SmartZikr: sign language Augmented Reality (AR) application / Fatin Mardhiah Zul Safaruddin - Zul Safaruddin, Fatin Mardhiah (2019)
The religious practice in everyday life is part of the manifestation of religion and belief of every human being. All Muslims, including the deaf, need to perform their religious obligations within their abilities. However, not much attention is given to people with disability, such as the deaf, with regards to observing their religious practices and in understanding the related problems that they face. Therefore, this project is intended to teach the deaf students in a Zikr Sign Language that usually are recited after every prayer. The objectives of this project are to identify the requirements of the SmartZikr application for deaf students, to design and develop SmartZikr application for the students by following the Mobile Application Development Life Cycle (MADLC) methodology during the development process that will use Unity software and C# as the coding language. The scope of this project consists of target user which is the deaf children, android mobile platform, the content which are Zikr Fatimah, sign language in Arabic and translation in Malay and the development phases that will be developed only until the testing phase. In recent years, there has been an increasing interest in applying Augmented Reality (AR) to create unique educational settings. So, an AR of 3D model will be made to gesture the sign language to make this application to be more interesting. A marker based detection technology, which are flash cards are used in this project to show the AR. Besides, this project will benefit several parties such as the deaf children as this application will help them to learn interactively. Besides, the AR designers and developers will also bring benefits as they are developing an application that beneficial to the community. For future recommendations, SmartZikr application may contain various Zikr that are generally used and available among the deaf communities. This can be done by adding extra menu buttons for users to choose other Zikr and adding 3D model that gesture other sign language. Lastly, SmartZikr application should be made available in iOS platform.